1964
DOI: 10.1085/jgp.48.1.73
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Proteolytic Enzymes on E. coli Phages and on Native Proteins

Abstract: Lambda coli phage is not inactivated by chymotrypsin, trypsin, or ficin. T 2 phage is slowly inactivated by high concentrations of a-, -, y-, or A-chymotrypsin, but not by trypsin or ficin. PI phage is slowly inactivated by a-, -, or y-chymotrypsin, or ficin, more rapidly by A-chymotrypsin, and much more rapidly by trypsin. Crystalline egg albumin, crystalline serum albumin, E. coli nucleoprotein, and yeast nucleoprotein are hydrolyzed slowly by a-chymotrypsin. Yeast nucleoprotein, like P phage, is hydrolyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Phages in the current study were also stable at a wide pH range (1–11) compared to the phages in other studies [ 49 , 60 ]. Niu et al [ 49 ] revealed that at pH 3 the titer of E. coli O157:H7 phage, AKFV33, dropped by 1.9 logs PFU mL −1 after 15 min and was undetectable after 2 h. In the current study, 3 of the 7 phages survived at pH 1, while all phages survived at pH 2 and 5 after 24 h, with minimal loss in viability.…”
Section: Discussionsupporting
confidence: 54%
“…Phages in the current study were also stable at a wide pH range (1–11) compared to the phages in other studies [ 49 , 60 ]. Niu et al [ 49 ] revealed that at pH 3 the titer of E. coli O157:H7 phage, AKFV33, dropped by 1.9 logs PFU mL −1 after 15 min and was undetectable after 2 h. In the current study, 3 of the 7 phages survived at pH 1, while all phages survived at pH 2 and 5 after 24 h, with minimal loss in viability.…”
Section: Discussionsupporting
confidence: 54%
“…Yamaki et al, 2014 observed that Myoviridae phages drastically lost phage activity (3.5 logs PFU mL − 1 ) after 60 min of incubation at 60°C. However, in the current study, the four phages show stability at temperature of 45 o C to 60 o C while there is no visible plaque observed at temperature above 60 o C. This is in line with the research work of Litt and Jaroni, 2017 on the isolation and physiomorphological characterization of Escherichia coli O157: H7-infecting bacteriophages recovered from beef cattle operations, where the phages remained stable for 24 h at a temperature range (40-60°C) and for 90 days in cold storage.At a wide pH range (2-9), phages in the current study were also stable compared to the phages in other studies(Niu et al, 2012;Northrop, 1964).Niu et al,…”
supporting
confidence: 58%
“…Experimental data available so far suggest, however, that bacteriophages demonstrate limited sensitivity to digestive enzymes (e.g., trypsin), but this differs between phage types. Notably, other proteases, such as proteinase K or papain, can easily inactivate phages resistant to trypsin (218)(219)(220)(221)(222)(223). Unfortunately, so far there are no experimental reports available to assess the effects exerted on phages specifically by tissue proteases or those enzymes secreted onto the mucosal surfaces of the lungs.…”
Section: Clearance Of Phages From Bodiesmentioning
confidence: 99%